PENINGKATAN PEMAHAMAN GURU DALAM PENYUSUNAN INSTRUMEN PENILAIAN DIMENSI PSIKOMOTOR MELALUI MODEL PEMBELAJARAN IN HOUSE TRAINING (IHT): SDN GUNUNGSARI 01 KECAMATAN MAESAN KABUPATEN BONDOWOSO (Mitra Pendidikan, 2020)
The low understanding of teachers in the preparation of skills dimension assessment instruments at SDN Gunungsari 01, Maesan sub-district is the focus of research. This is reinforced by the results of interviews conducted before the research was carried out which stated that teachers still had difficulty in preparing and developing assessments on the aspects of skills. Meanwhile, the results of the teacher's product assessment in the preparation of the skills dimension assessment instrument before the study were an average of 59 with unfavorable criteria. While the results of observations on the implementation of the assessment of the skills aspects before the study averaged 61 with good enough criteria. The conclusion of the results of this study using the in-house training (IHT) learning model shows an increase in teacher understanding in developing skills dimension assessment instruments. This conclusion is supported by the results of the teacher's product assessment in the form of a skills aspect assessment plan, namely the average silbus in cycle1 is 82 with good criteria, while in cycle 2 the average is 90 with very good criteria. While the results of the assessment of the implementation of the assessment of skills aspects in cycle 1 an average of 78 with good criteria, while in cycle 2 an average of 89 with very good criteria. The results of the interview at the end of cycle 2 explained that the teacher was able to independently compile the skill dimension assessment instrument according to the assignment in class, was skilled in making the skill dimension assessment, was able to use all the techniques of performance assessment instruments, projects, products, portfolios, and written and there is a strong desire to plan and develop the assessment of skills aspects so that it can make it easier to make good assessments.